SUMBER DAYA MANUSIA DAN TINGKAT PENGANGGURAN DI PROVINSI JAWA TENGAH - Dwi Mahroji; Saiful Anwar (STIE Muhammadiyah Jakarta, 2020)
The purpose of this study is to analyze how the influence of the quality of human resources (HR) seen from the human development index (HDI) affects the unemployment rate in Central Java in 2008-2012. Data analysis in this study uses the Multiple Linear Regression Method. The results showed an interesting result, namely that the population had a significant negative effect on unemployment. The regression results state that the increase in the number of residents will increase unemployment. These results indicate that population growth in the province of Central Java helped drive the province's economy.